Looking for the Evidence: Value of Health Informatics. Editorial - Séroussi, B.; Jaulent, M.-C.; Lehmann, C.U. (Yearbook of Medical Informatics, 2013)
Objectives: To provide an editorial introduction to the 2013 IMIA Yearbook of Medical Informatics with an overview of its contents and contributors.Methods: A brief overview of the main theme, and an outline of the purposes, contents, format, and acknowledgment of contributions.Results: Health information technology (HIT) is currently widely implemented to improve healthcare quality and patient safety while reducing costs. Although these benefits are expected and largely advertised, the evidence for these benefits is still missing. Unintended consequences are often reported and some applications have been shown to be wasteful, harmful, and even fatal. Evidence-based health informatics has been defined as “the conscientious, explicit and judicious use of current best evidence when making decisions about the introduction and operation of information technology in a given health care setting”. The 2013 issue of the IMIA Yearbook highlights important contributions about the significant challenges that arise from the assessment of HIT solutions. Progress towards evidence-based health informatics is identified to elicit what works, what doesn't work, and why. In an environment where resources are limited, budgets lower than in past years, and the need to improve care is becoming ever more pressing, focusing on this topic should guide institutions and providers in the implementation of the best health information technology.Conclusion: This overview of progress and current challenges across the spectrum of the discipline shows many great examples of evidence that have been gathered on the effectiveness of HIT. However, evidence remains limited and a significant work should be conducted to improve the development, testing, and implementation of HIT applications.
Keywords: Editorial; 2013 IMIA Yearbook of Medical Informatics; evidencebased health informatics; surveys of biomedical informatics; IMIA and its societies